2008
DOI: 10.7326/0003-4819-148-11-200806030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Declining Incidence of Hepatocellular Carcinoma in Osaka, Japan, from 1990 to 2003

Abstract: The incidence of HCC in Osaka started to decrease by 2000, mainly because of decreased HCV-related HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 16 publications
0
104
2
2
Order By: Relevance
“…In Japan, HCV is the main risk factor for HCC (25) and significant declines in liver cancer incidence rates in this country have been attributed to reduced transmission of HCV since the 1950s and 1960s as a result of the change in blood bank donation policies from a paid to voluntary system as well as to more stringent legal penalties deterring parenteral amphetamine use, which had increased after the devastation to the country in World War II (10). Historically, the primary risk factors for liver cancer in China and the Philippines have been HBV infection and dietary aflatoxin exposure (China only), and these 2 factors have been shown to have a synergistic effect on HCC (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, HCV is the main risk factor for HCC (25) and significant declines in liver cancer incidence rates in this country have been attributed to reduced transmission of HCV since the 1950s and 1960s as a result of the change in blood bank donation policies from a paid to voluntary system as well as to more stringent legal penalties deterring parenteral amphetamine use, which had increased after the devastation to the country in World War II (10). Historically, the primary risk factors for liver cancer in China and the Philippines have been HBV infection and dietary aflatoxin exposure (China only), and these 2 factors have been shown to have a synergistic effect on HCC (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from a variety of international sources have reported trends in liver cancer incidence rates, including increasing trends in developed countries with historically low liver cancer incidence rates and decreasing trends in areas with the highest observed liver cancer incidence in the world (7)(8)(9)(10)(11). However, these studies were limited because they were country-or region-specific (8)(9)(10)(11) or because they were based on old data sets (7).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, these data need to be interpreted carefully and it appears to be unlikely that HCV is a key determinant in the development if IBM. The increasing incidence of IBM in Japan is in strong contrast to the decreasing incidence in HCV infections 66, 67, 68. Moreover, countries with relatively high incidence rates of HCV infections belong to the regions that are stricken the least by IBM 26, 30, 61, 69, 70, 71.…”
Section: Pathomechanisms In Ibmmentioning
confidence: 98%
“…The liver cancer mortality in young people in Qidong demonstrates a continuously falling trend . The incidence of HCC in Osaka started to decrease by 2000, mainly because of decreased HCV-related HCC (Tanaka et al, 2008).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%